Advances in Treatment Options for Psoriasis - Sudesh S Raju (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2015)
Psoriasis is a skin disease that is evidenced primarily by plaques which can be seen throughout the body. Genetic predisposition that combines with an environmental trigger of the immune system is believed to be the root cause of psoriasis. This leads to signaling factors which coordinate the progression of inflammation and psoriatic plaques. Psoriatic patients commonly use topical agents, phototherapy, and systemic agents; however, biological therapies have become increasingly popular. This is primarily due to recent advances in the study of psoriasis which have shown that monoclonal antibodies and dimeric fusion proteins inhibit key signaling molecules within the inflammatory cascade such as TNFa, IL-12 and IL-23. This article reviews the advances made to understand the role of TNFain the progression of psoriasis, discusses treatment options such as topical agents, phototherapy and systemic agents, and then compares a variety of monoclonal antibodies and dimeric fusion proteins as biological therapies.